Competent to counsel - Adams, Jay Edward (Phillipsburg, NJ Presbyterian and Reformed Publishing Co., 1970)
Includes bibliographical references and indexes.
The prequel and companion volume to The Christian counselor's manual, which see also.
Keywords: Pastoral counselling